Infant size and the association between maternal circulating angiogenic factors and preeclampsia. (May 2018) - Honigberg, Michael; Seely, Ellen; Thomas, Ann; Lim, Kee-Hak; Parry, Samuel; McElrath, Thomas
Abstract Objective: To assess the effect of infant size as a marker of placental function on the association between preeclampsia and the ratio of soluble fms-like tyrosine kinase 1 (sFlt-1) to placental growth factor (PlGF). Study design: The angiogenic factors sFlt-1 and PlGF were measured prospectively at 26 weeks gestation in 2322 women. Pregnancies were stratified by whether or not they were complicated by preeclampsia, the timing of delivery, and birthweightZ -score. Result: Independent of preeclampsia status, women with small infants (Z  < -1.0) have an increased sFlt-1/PlGF ratio, and women with large infants (Z  > 1.0) have a decreased ratio. Among pregnancies yielding small infants, the sFlt-1/PlGF ratio is markedly elevated in preeclamptic pregnancies requiring delivery before 37 weeks (110.0 vs. 17.9, p  < 0.0001) but not in preeclamptic pregnancies delivered at term. The strength of the association between preeclampsia and the sFlt-1/PlGF ratio is increased for small infants compared to normal-sized or large infants. Conclusion: The sFlt-1/PlGF ratio in the late second trimester is similarly elevated in women with preeclampsia and in women with small infant size and more markedly elevated in a syndrome of placental dysfunction characterized by preeclampsia, preterm delivery, and growth restriction.